Pengaruh Kompetensi Sumber Daya Manusia dan Tekanan Eksternal Terhadap Kualitas Laporan Keuangan Pemerintah Daerah (Studi Kasus Pada Dinas Pendapatan Pengelola Keuangan dan Aset Daerah Kota Sawahlunto) - Rinka Merantika; Randy Heriyanto (Akuntansi dan Manajemen, 2017)
This study aims to determine the effect of human resource competencies and external pressure on the quality of financial statements. Research uses a quantitative approach. Data collection of this study uses questionnaire surveys. Questionnaires were submitted to 52 Revenue Service Officers of Regional Finance and Asset Management (DPPKAD) of Sawahlunto City who were Civil Servants (PNS), as many as 48 questionnaires (92%) were returned fully and could be processed. The collected power is processed using a smart PLS 2.0 program. Data analysis using the measurement model (outer model) and structural model (inner model), first carried out the Successive Interval Method (MSI). The results showed that the competence of human resources and external pressure had a positive effect on the quality of financial statements. Suggestions for further research are expected to expand the object of research and add other variables not included in this study.